Potential industrial applications of photo/electrocatalysis: Recent progress and future challenges - Jinhao Li; Jing Ren; Shaoquan Li; Guangchao Li; Molly Meng-Jung Li; Rengui Li; Young Soo Kang; Xiaoxin Zou; Yong Luo; Bin Liu; Yufei Zhao (Green Energy & Environment, 2024)
Nowadays, the rapid development of the social economy inevitably leads to global energy and environmental crisis. For this reason, more and more scholars focus on the development of photocatalysis and/or electrocatalysis technology for the advantage in the sustainable production of high-value-added products, and the high efficiency in pollutants remediation. Although there is plenty of outstanding research has been put forward continuously, most of them focuses on catalysis performance and reaction mechanisms in laboratory conditions. Realizing industrial application of photo/electrocatalytic processes is still a challenge that needs to be overcome by social demand. In this regard, this review comprehensively summarized several explorations in the field of photo/electrocatalytic reduction towards potential industrial applications in recent years. Special attention is paid to the successful attempts and the current status of photo/electrocatalytic water splitting, carbon dioxide conversion, resource utilization from waste, etc., by using advanced reactors. The key problems and challenges of photo/electrocatalysis in future industrial practice are also discussed, and the possible development directions are also pointed out from the industry view.